PENERAPAN HUKUM ADAT DALAM MENYELESAIKAN TINDAK PIDANA PERZINAHAN YANG DILAKUKAN OLEH REMAJA DI KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - Arif Yuliansyah; Mexsasai Indra; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Adolescence is a phase of development between childhood and adulthood. In adolescene, it is the desire to try, to follow trends and lifestyles, and have enormous fun. So, a person’s development in childhood and adolescene will shape the person’s self development in adulthood. Article 284 of KUHP cannot be a legal basis for adolescents who commit adultrety, there fore the process of adultery committed by adolescents is completed through customary law. Customary law is an institution that forms villages that have formed themselves because of the habits of the local community. Customary law priorities the settlement by deliberation and consensus in resolving these criminal acts. The purpose of this thesis research is : fisrt, To find out the process of settlement of adultery committed by adolescents in Mandah sub-district Indragiri Hilir district. Second, to find out legal consequences of the settlement of adultery crimes committed by adolescents through customary law. This type of research of sociological legal research. Empirical juridical research or sociological legal research is research conduted directly on site or in the field to obtain data to provide a complete and clear picture of the problem in question. This research was conduted in Mandah sub-district Indragiri Hilir district. The data used primary data, secondary data, and tertiary data. Data collection techniques using interviews and literature study.Based on the results of the study and discussion it can be concluded that first, the process of resolving criminal acts of adultery committed by adolescents in Mandah sub-districh. As for the settlement process through customary law that is : One, as a family. Two, in consultation with customary leaders and community leaders. Second, Legal consequences are customary legal liability by Ninik Mamak as law enforcers by priorotizing consensus adreement in determining customary punishment that is not contrary to applicable legal norms. Suggestion, the results in the flow of the settlement process of adultery committed by adolescents in Mandah sub-distrith are final, prioritizing common interests rather that individuals so that justice is not created and is not biased, and villages make village regulations that forbid teenagers or young men and women from carrying out activities above 10 pm except held by the village of scholl. National KUHP must pay attention to the values prevailing in society. Other than that, law enforcers are expected to be able to act fairly in the application of sanctions for those who commit adultery.Keywords: The process of resolving criminal acts of adultery committed by adolescents through customary law